(untitled) (Applied Biological Research, 2023)
Nonsterile pharmaceutical finished products are not manufactured through aseptic processes so are not completely free from microbial contaminations, which can impact their efficacy due to the degradation of active ingredients. The aim of present study was to enumerate, isolate and identify the microbial contaminations in non-sterile liquid finished pharmaceutical dosage forms. A total of 50 nonsterile liquid products were collected from different pharmacies across Lahore city, Pakistan. Pour plate method was used to test the total microbial count as per USP guidelines. The results showed a microbial count of 140 cfu mL-1in nutraceuticals manufactured liquid dosage form, 60 cfu mL-1in multinational products, 120 cfu mL-1in registered herbal products, and 390 cfu mL-1inon-registereherbal liquid products. Major bacterial contaminants isolated from allopathic (local and multinational) products and herbal (registered and non-registered) products are reported.